Program Models, Pre-service Teachers, and Emergent Bilingual Instruction - (:unkn) unknown (My University, 2017)
It is estimated by the year 2030, over 40% of the K-12 population in U.S. schools will be children whose first language is not English (U.S. Census Bureau, 2007; Shin & Ortman, 2011). This situation has potential academic consequences for emergent bilingual students (EBS) attending schools without adequate accommodations. The issue of teachers who are underprepared to meet the needs of EBS contributes to the academic consequences absorbed by this K-12 population, and to the social and cultural cycle of oppression for this marginalized group. Thus, integrating knowledge, skills, and dispositions (KSDs) beneficial for meeting the needs of EBS becomes imperative for pre-service program models. This dissertation served as a ship navigating the deep and wide learning opportunities offered by three distinct pre-service program models. Participants from three program models: Intentionally Integrated, Traditional, and Student-Selected Add-On asserted ways in which their program model provided learning opportunities for development of KSDs beneficial to EBS. Differences in program models shaped pre-service teachers’ opportunities to learn the KSDs required for working with emergent bilingual students, which in turn, determined what they enacted in classrooms. As such, program model opportunities interrupting the cycle of oppression for EBS emerged from the study. This interruption reemphasizes why intentional integration of learning opportunities useful for developing KSDs beneficial to EBS must occur pre-service program models.
Keywords: Critical Theory; Emergent Bilingual Instruction; ESL; Pre-service Program; Pre-service Teachers; Teacher Candidates